Experiences of using surveillance cameras as a monitoring solution at nursing homes: The eldercare personnel's perspectives - Maria Emilsson; Christina Karlsson; Ann Svensson (BMC, 2023)
Abstract Background As the number of older people increases, so does the need for care. However, the workforce in eldercare cannot increase at the rate required to match the needs. Welfare technologies, such as surveillance cameras, can replace physical visits and be used at night to monitor older people in order to keep them safe, while not disturbing their sleep. The aim of the paper is to analyze obstacles and opportunities associated with implementation and use of surveillance cameras at nursing homes from the perspectives of the practitioners who use the technology, their working environment and the conditions of the older people with cognitive impairment who live in nursing homes. Methods Individual semi-structured interviews were conducted with the eldercare personnel at nursing homes to understand their experiences of implementation and use of surveillance cameras. The transcribed interviews were analyzed using qualitative content analysis. The consolidated criteria for reporting qualitative research (COREQ) was used as a guidance tool. Results The results show that the eldercare personnel experienced lack of adequate information, education and support related to using surveillance cameras. Several benefits are highlighted, such as better working environment and that the residents were not unnecessarily disturbed at night. However, the results also show that it is important to clarify that surveillance cameras cannot replace the human presence. Conclusions The conclusions from this study are the importance of prerequisites for implementation, and that using surveillance cameras contributed to improvements in the working environment at night and created possibilities to maintain security and integrity for older people living in nursing homes.